2017
DOI: 10.3892/ol.2017.6229
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to epithelial growth factor receptor tyrosine kinase inhibitors in a patient with transformation from lung adenocarcinoma to small cell lung cancer: A case report

Abstract: First-generation epithelial growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have markedly improved the treatment of non-small cell lung cancer (non-SCLC) with EGFR-sensitive mutations. However, acquired resistance to these drugs was inevitable. The transformation of lung adenocarcinoma to SCLC following treatment with EGFR-TKIs is a rare phenomenon that contributes to resistance to EGFR-TKIs. The present case concerns a 74-year-old man previously diagnosed with and treated for pneumonia; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…AKT activation is a convergent feature of acquired EGFR tyrosine kinase inhibitor resistance, across a spectrum of diverse, established upstream resistance mechanisms. Studies have shown that AKT inhibition, specifically, could moreuniformly enhance response and survival in patients with high pAKT levels who are at high risk for AKT-mediated resistance, as this distinct approach has the unique potential to combat the otherwise profound heterogeneity of molecular resistance events that are present in EGFR-mutant NSCLC patients with acquired EGFR-TKI resistance to improve their outcomes [ 139 , 140 ].…”
Section: Tki Acquired Resistancementioning
confidence: 99%
“…AKT activation is a convergent feature of acquired EGFR tyrosine kinase inhibitor resistance, across a spectrum of diverse, established upstream resistance mechanisms. Studies have shown that AKT inhibition, specifically, could moreuniformly enhance response and survival in patients with high pAKT levels who are at high risk for AKT-mediated resistance, as this distinct approach has the unique potential to combat the otherwise profound heterogeneity of molecular resistance events that are present in EGFR-mutant NSCLC patients with acquired EGFR-TKI resistance to improve their outcomes [ 139 , 140 ].…”
Section: Tki Acquired Resistancementioning
confidence: 99%
“…Considering our case and the prior literature, clinicians should be aware that SCLC transformation can occur for all EGFR-TKI generations. Serum NSE levels may be useful for detecting early SCLC transformation [ 9 ]; however, tests for tumor markers showed normal levels of serum NSE and proGRP in the current case.…”
Section: Discussionmentioning
confidence: 89%
“…11 As for the criteria which may lead to suspect a histological transformation is the rapid increase of neuroendocrine markers in blood, as well as the poor clinical response to the treatment established, making new biopsies fundamental, especially to focus pharmacologic management. 12 It is worth mentioning that in these cases, the liquid biopsy, another diagnostic option approved for the follow-up of patients with mutations in EGFR to monitor the appearance of resistance mutations, with a sensitivity for the Thr790Met mutation of up to 70%, would not be indicated, as the evaluation of the tissue is required to perform the histological diagnosis. 13,14 In small cell carcinoma of the lung, the standard chemotherapeutic treatment is based on the combination of Cisplatin or Carboplatin plus Etoposide, with good response, both for the disease in early stages and for the advanced stage.…”
Section: Discussion/conclusionmentioning
confidence: 99%